Shock and Flexural Strength of Composite Materials Reinforced by Kevlar Fiber - Mustafa A. Rajab (Journal of Global Pharma Technology, 2016)
Composite materials in this regard represent nothing but a giant step in the ever-constant endeavor of optimization in materials.  The research aims to study the mechanical properties (shock strength and Flexural strength) of composite materials (epoxy resins with phenolic formaldehyde resin) supported by graphite or silica particles or both, and reinforced with Kevlar fibers.